HUBUNGAN KOORDINASI MATA-KAKI DAN KELINCAHAN TERHADAP HASIL DRIBBLING SEPAKBOLA SSB TAMA PUTRA PEKANBARU - Dedy kurniawan; Drs.Saripin, M.Kes, AIFO '; Kristi Agust, S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study is the lack of dribbling skill it is presumably because the ankle coordination and the agility are not maximized. This study was conducted to find out the correlation between the ankle coordination and the agility towards the skill of soccer dribbling of SSB Tama Putra Pekanbaru. The sample of this research was 20 soccer players of SSB Tama Putra Pekanbaru. In order to get the sample, the researcher used total sampling. The instrument in this research was ankle coordination test which aimed to measure the students’ ankle coordination in moving, the agility of dogging run test which aimed to measure the skill of changing the direction of running and dribbling test used soccer dribbling. Before analyzing the data, the normality test should be conducted in advance by using liliefors test and regression linearity test at significant level 0,05. The hypotheses are 1. The correlation of ankle coordination towards the skill of soccer players dribbling of SSB Tama Putra. 2. The correlation of the agility towards the skill of soccer players dribbling of SSB Tama Putra Pekanbaru. 3. The correlation between ankle coordination and the agility toward the skill of soccer payers dribbling of SSB Tama Putra Pekanbaru. Ankle coordination (X) to dribbling skill (Y) obtained result rcount = 0,198 when compared with the critical value rtable= 0,456, then the result is rcount<rtable at the level of significant testing = 0, 05. The result obtained that there is no significant correlation between the ankle coordination to dribbling skill. The product moment correlation analysis between the ankle coordination (X2) to the dribbling skill (Y) obtained the result rcount = 0,264 which compared with the critical value rtable = 0,456 obtained the result rcount<rtable at the level of significant testing 0, 05. The result obtained that there is no significant correlation to the agility of dribbling skill. The analysis of multiple correlation between the ankle coordination (X1) and the agility (X2) of the dribbling skill (Y) obtained value rcount= 0,398 and when compared with the critical value rtab=0,456 then obtained rcount<rtable at the level of significant testing = 0,05. Based on these the result, there is no significant correlation between the ankle coordination to dribbling skill. In conclusion, there is a correlation between the ankle coordination and the agility to dribbling skill even though there is no significant result of this orrelation.Key Word: Ankle coordination and agility to dribbling skill2HUBUNGAN